Tissue-specific signatures in tick cell line MS profiles - Loginov, Dmitry S; Loginova, Yana F; Dycka, Filip; Böttinger, Katharina; Vechtova, Pavlina; Sterba, Jan (Parasites & vectors, 2019)
BACKGROUND: The availability of tick in vitro cell culture systems has facilitated many aspects of tick research, including proteomics. However, certain cell lines have shown a tissue-specific response to infection. Thus, a more thorough characterization of tick cell lines is necessary. Proteomic comparative studies of various tick cell lines will contribute to more efficient application of tick cell lines as model systems for investigation of host-vector-pathogen interactions. RESULTS: Three cell lines obtained from a hard tick, Ixodes ricinus, and two from I. scapularis were investigated. A cell mass spectrometry approach (MALDI-TOF MS) was applied, as well as classical proteomic workflows. Using PCA, tick cell line MS profiles were grouped into three clusters comprising IRE/CTVM19 and ISE18, IRE11 and IRE/CTVM20, and ISE6 cell lines. Two other approaches confirmed the results of PCA: in-solution digestion followed by nanoLC-ESI-Q-TOF MS/MS and 2D electrophoresis. The comparison of MS spectra of the cell lines and I. ricinus tick organs revealed 29 shared peaks. Of these, five were specific for ovaries, three each for gut and salivary glands, and one for Malpighian tubules. For the first time, characteristic peaks in MS profiles of tick cell lines were assigned to proteins identified in acidic extracts of corresponding cell lines. CONCLUSIONS: Several organ-specific MS signals were revealed in the profiles of tick cell lines.
Keywords: Animals; 2D gelová elektroforéza; Female; buněčné linie; slinné žlázy; klíště; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Salivary Glands; ženské pohlaví; Tandem Mass Spectrometry; proteomika; hmyzí proteiny; Cell Line; Proteomics; tandemová hmotnostní spektrometrie; Electrophoresis, Gel, Two-Dimensional; Insect Proteins; spektrometrie hmotnostní - ionizace laserem za účasti matrice; zvířata; Ixodes